Development of eco-friendly biodegradable superabsorbent materials obtained by injection moulding. (10th October 2018) - Perez-Puyana, V.; Felix, M.; Romero, A.; Guerrero, A.
Abstract: The development of eco-friendly materials requires a deep knowledge of physical, chemical and functional properties of biopolymers and fillers. Soy protein (SPI), which is one of the cheapest protein in global markets, was used in combination with montmorillonite (MMT-Na + ) to obtain fairly attractive green biocomposite superabsorbent materials, leading to biodegradable superabsorbent materials. Natural MMT-Na + was used since it is widely available as micron-size tactoids and gives rise to highly functional nanoparticles. However, the dispersion of such particles within a polymer structure is complex, showing a high impact on techno-functional properties. An easy-scalable processing technique was used with a mixing stage to obtain dough-like materials which were subjected to an injection-moulding process that led to biodegradable biocomposite materials. The structure of dough-like materials was characterized by scanning electron microscopy and X-Ray diffraction, whereas mechanical properties of green biocomposites were evaluated by dynamic mechanical analysis (DMA) and tensile tests. Moreover, the techno-functionality of the new materials obtained was determined by means of water uptake capacity (WUC). Results suggested that the addition of nanoclay led to an increase of the elastic modus although the overall improvement of mechanical properties is not clear. Interestingly, water uptake capacity was greatly enhanced. In this sense, these green biocomposites could be considered as an excellent candidate for the development of novel bio-based superabsorbent materials. Graphical abstract: Image